STRATEGI PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR PADA ERA DISRUPSI DIGITAL : TINJAUAN PUSTAKA SISTEMATIS - Putri Zain, Bella; Hafidza, Hikmah; Juita Harun, Gustiayu (Study program PGSD FKIP Universitas Bung Hatta, 2025)
This study was conducted with the aim of identifying appropriate strategies to improve character education for elementary school students. The research employed a systematic literature review approach. Data were collected from various sources, synthesized, and analyzed to draw comprehensive conclusions. The results indicate the critical importance of character education in the era of technological disruption, which must be nurtured from the elementary school level. Furthermore, this study examines the roles of teachers, parents, and the environment in achieving this goal. Several strategies for teachers to implement effective character education in the future are presented. These strategies include enhancing teachers' digital literacy through socialization and training, fostering collaboration with parents and communities, integrating character values into the learning process, and developing digital-based curricula. If all elements and stakeholders are optimally involved, the goal of realizing the 2045 Golden Generation is within reach. In conclusion, creating a digitally competent future generation is inseparable from character education rooted in the spirit of Pancasila.